Kajian Arang Aktif Sekam Padi Untuk Penurunan Kandungan Fe Di Lokasi Masyarakat Skala Rumah Tangga - Marwan Kurniawan; Helina Helmy; Agus Sutopo (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
To improve water quality, rice husks are soaked in activated carbon to treat water. This activated carbon works through an absorption mechanism. This study tested the effectiveness of rice husk activated carbon in reducing iron concentration. Water is an element of the environment that is very important for human life and is used for various purposes, including household, industrial, and agricultural purposes. The quality of water used must meet physical, chemical and biological requirements. Many materials can be used and processed into activated charcoal, in this study, researchers used rice husk activated charcoal, where rice husk is very abundant and abundant so it is easy to obtain. The results of the study, the iron content in water experienced the greatest decrease of 0.06 mg/L after soaking for 120 minutes, followed by a decrease of 1.78 mg/L (96%), thus making the iron content in water below the specified value. Thus, rice husk activated carbon effectively reduces iron content in water.Thus, it can be confirmed that activated charcoal from rice husks is effective in reducing iron levels in water.